2015
DOI: 10.1111/jnc.13243
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 signaling reduces neuroinflammation during hepatic encephalopathy

Abstract: Hepatic encephalopathy (HE) is a serious neurological complication of acute and chronic liver failure. Expression of the neurosteroid/bile acid receptor TGR5 has been demonstrated in the brain and is thought to be neuroprotective. However, it is unknown how TGR5 signaling can influence the progression and associated neuroinflammation of HE. HE was induced in C57Bl/6 mice via intraperitoneal injection of azoxymethane (AOM) and tissue was collected throughout disease progression. TGR5 expression was elevated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 51 publications
3
83
0
3
Order By: Relevance
“…Moreover, we found that the transcription of GPBAR1/TGR5 was induced by TUDCA or LPS in cultured microglia. Our results are in agreement with a recent publication by McMillin et al () who showed that TGR5 was expressed in the cerebral cortex of mice. Moreover, the expression of TGR5 was higher in mouse brain following a model of hepatic encephalopathy compared to controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, we found that the transcription of GPBAR1/TGR5 was induced by TUDCA or LPS in cultured microglia. Our results are in agreement with a recent publication by McMillin et al () who showed that TGR5 was expressed in the cerebral cortex of mice. Moreover, the expression of TGR5 was higher in mouse brain following a model of hepatic encephalopathy compared to controls.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, a small molecule agonist of the bile acids receptor GPBAR1/TGR5 has exerted the same anti‐inflammatory effect on myeloid cell activation in vitro (Lewis et al, ) as shown by other agonists like TUDCA (Yanguas‐Casás et al, ) and betulinic acid (McMillin et al, ) on microglia. Mice treated with that TGR5 agonist showed reduced monocyte and microglial activation and reduced trafficking of monocytes and T cells into the CNS, correlating with a reduced clinical score in an animal model of experimental autoimmune encephalomyelitis (EAE, Lewis et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…It causes neuroinflammation. The activation of TGR5 by betulinic acid decreases neuroinflammation via neuron and microglia paracrine signaling during HE (McMillin et al, 2015, Table 1). Last year, our group found that TGR5 activation also suppresses gastric inflammation (Guo et al, 2015a).…”
Section: Tgr5 and Different Diseasesmentioning
confidence: 99%
“…Bile acids have been reported throughout the brain3240 and bile acid receptor and transporter expression in the brain has also been established323942596061. The fact that bile acid receptors and transporters are found throughout the brain suggests the possibility that bile acids might be able to modulate neuronal function38.…”
Section: Discussionmentioning
confidence: 99%
“…Blood brain barrier (BBB) breakdown can facilitate bile acid entry into the brain38. Once in the brain, bile acids can be beneficial39 or detrimental3238 depending on the physiological conditions, as well as the type and location of the receptors to which they bind40. Bile acids receptors may be cell-surface or nuclear, and have tissue-specific effects related to cholesterol synthesis, bile acid synthesis, and other g-protein mediated effects4142.…”
mentioning
confidence: 99%